Risk as an Indicator of Uncertainty in the Innovative Supply Chain of Enterprises - Kozlov, Anatoly; Tamer, Olga; Lapteva, Svetlana; Kruchinin, Sergey (International Journal of Supply Chain Management, 2018)
The formation of professional competence in modeling of innovative supply chain of enterprises has a number of problems associated with the instability and variability of the external environment of decision-making systems that generate uncertainty and increase the risk in decision-making. The indicator of uncertainty in such situations is the concept of